2003
DOI: 10.1023/a:1023741518385
|View full text |Cite
|
Sign up to set email alerts
|

Untitled

Abstract: Reactive oxygen species play a key role in intestinal inflammation, although interventional studies using antioxidants have shown only weak beneficial effects both in humans and animals. Hence, our aim was to examine the possible beneficial effect of the antioxidant 2-mercaptoethane sulfonate (Mesna) on experimental colitis. Colitis was induced in rats by intrarectal instillation of trinitrobenzene sulfonic acid (TNB) followed immediately by intrarectal Mesna or saline, administered for 14 days, twice daily. A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2005
2005
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(3 citation statements)
references
References 36 publications
0
3
0
Order By: Relevance
“…MyD88 signal is an important adaptor protein in the process of TLR4 signal transduction, and it is also the upstream signal molecule of the NF-kB signaling pathway, which in turn triggers the signal cascade, resulting in the activation of downstream NF-κB [53]. NF-κB is a marker of intestinal mucosal infection, and the level of NF-κB in colon tissue can reflect the severity of UC disease [54]. Studies have also shown that NF-κB is over-activated in the process of UC, leading to the secretion of pro-inflammatory cytokines, and the accumulation of these inflammatory cytokines is considered to be an important factor in the pathogenesis of colitis [55,56].…”
Section: Discussionmentioning
confidence: 99%
“…MyD88 signal is an important adaptor protein in the process of TLR4 signal transduction, and it is also the upstream signal molecule of the NF-kB signaling pathway, which in turn triggers the signal cascade, resulting in the activation of downstream NF-κB [53]. NF-κB is a marker of intestinal mucosal infection, and the level of NF-κB in colon tissue can reflect the severity of UC disease [54]. Studies have also shown that NF-κB is over-activated in the process of UC, leading to the secretion of pro-inflammatory cytokines, and the accumulation of these inflammatory cytokines is considered to be an important factor in the pathogenesis of colitis [55,56].…”
Section: Discussionmentioning
confidence: 99%
“…Many factors have been implicated in the pathogenesis of UC, such as neutrophil infiltration and overproduction of proinflammatory mediators, including cytokines, arachidonate metabolites, and reactive oxygen metabolites. Proinflammatory cytokines had significantly higher expression and antiinflammatory cytokines had lower expression in the colonic mucosa of UC patients (Ademoglu et al 2004;Danese et al 2004;Shusterman et al 2003;Woodruff et al 2005). Because the increasing lipid peroxidation and mucosal production of reactive oxygen mediators were described in colorectal biopsy specimens of patients with UC, attention has been focused on the role of free radicals in the pathogenesis of UC.…”
Section: Discussionmentioning
confidence: 99%
“…Inflammatory stimuli induce macrophages to secrete TNF-α, which further activates macrophages and nuclear transcription factors such as NF-κB, thereby promoting the release of other inflammatory factors. 21 Apoptosis plays an important role in the late stage of inflammatory reaction, and TLR4/NF-κB is also a key signal to inhibit intestinal epithelial cell apoptosis. 22,23 Studies have shown that TLR4 is involved in the signal pathway of NF-κB nuclear translocation induced by LPS stimulation.…”
Section: Discussionmentioning
confidence: 99%